Unpacking the cultural paradox of attentive care for institutionalized people with intellectual disabilities. (November 2022) - Chen, Bo-Wei; Chou, Yueh-Ching; Chi, Heng-Chang
Abstract: This study contributes to the under-researched area of culture in institutional care for people with intellectual disabilities in an East Asian context. Drawing upon in-depth interviews with 20 women frontline care workers for institutionalized people with intellectual disabilities in Taiwan, we examined culture-specific caring relations such as the fictive kinships of Confucian care ethics (i.e., respect for elders and affection for the young), the charity paradigm, and religious compassion, which can induce attentive and respectful care in institutional spaces but also relegate residents to stigmatized subordination in a hierarchy of caring relations and legitimatize the voluntary exploitation of women workers. In situating the relational nature of care and the dis-enabling potentials of culture at the disability-care-place intersection, we promote an ethics of engagement that values and dignifies both recipients and providers of care. Highlights: Situating East Asian culture in institutional care for people with intellectual disabilities to address its under-examined role in a relational geography of disability. Explicating the moral significance of culture in approaches to disability, care and place. Exploring how attentive and dignified care are culturally enacted in institutionalized and potentially disabling spaces. Illuminating the paradoxical cultural logic of care that entails both dignity and social hierarchies. Highlighting the inextricable role of culture in reconceptualizing good care and care-ful geographies.